Sulfur-rich antimonselite, Sb2(Se,S)3 in the Se-bearing mineral association from the Pribram uranium and base metal ore district, Czech Republic - Skacha,P.; Plasil,J.; Sejkora,J.; Golias,V. (Journal of Geosciences, 2015)
Antimonselite from the new occurrence, Pribram uranium-base metal ore district (Central Bohemia, Czech Republic), has been studied by means of electron microprobe and X-ray diffraction. Antimonselite crystals, reaching up to 1.5 mm across, were rarely found in the calcite gangue with uraninite in association with clausthalite, tiemannite, hakite, tetrahedrite, Se-rich chalcopyrite, permingeatite, Se-rich and Se-analogue of chalcostibite and dzharkenite. Based on electron-microprobe analyses, the empirical formula of the studied antimonselite (mean of 7 point analyses, based on 5 apfu) is (Sb2.06Cu0.01)Σ2.07(Se2.47S0.46)∑2.93. The studied S-rich antimonselite is orthorhombic, the space group Pnma, with a = 11.7156(3), b = 3.9514(11), c = 11.5645(3) Å, V = 535.36(15) Å3, and Z = 4. The structure was refined from the single-crystal X-ray data to R1 = 0.0143 for 634 reflections [with Iobs > 3σ(I)]. The structure of S-rich antimonselite is isotypic to that of stibnite. Sulfur was found to be entering the selenium sites regularly without any evidence of preferential ordering of the atoms at the different sites.
Keywords: antimonselite; Se-chalcostibite; crystal structure; X-ray diffraction; Pribram; Czech Republic